Slade eaudiobook - McCarty, Sarah (Shadow Wranglers, 2011)
As the backbone of The Renegades' defense, vampire technological genius Slade Johnson hasn't met a problem he couldn't solve. But when Slade is tasked with saving the life of his nephew, he must get in bed with the one woman who has the power to destroy them all: his enemy...his mate.